Analysis Accountability and Transparency Village Fund Management in Sub-districts West Suli Regency Luwu - Muhammad Topan Pratama; Ruliaty; Alamsjah (Journal JEKAMI, 2026)
This study examines the implementation of accountability and transparency in village fund management in Salubua Village, West Suli District, Luwu Regency, Indonesia. Effective village fund governance is essential for promoting good governance, enhancing public trust, and ensuring that public resources are managed efficiently and in accordance with applicable regulations. The study aims to evaluate whether the management of village funds has complied with the principles of accountability and transparency throughout the stages of planning, implementation, administration, reporting, and accountability as stipulated in the Indonesian Minister of Home Affairs Regulation No. 20 of 2018 concerning Village Financial Management. This research employed a qualitative descriptive approach. Primary data were collected through semi-structured interviews with key informants, including the Village Head, Village Secretary, and Village Treasurer, while secondary data were obtained from official village financial documents, planning reports, and accountability reports. The data were analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings reveal that village fund management in Salubua Village has generally been implemented in accordance with the prevailing regulatory framework. Accountability is reflected in the proper preparation of financial reports, systematic administrative procedures, and compliance with financial management standards. Transparency is demonstrated through community participation in village development planning meetings, public disclosure of budget information, and the installation of information boards detailing village fund allocations and realizations. The study concludes that effective accountability and transparency practices contribute significantly to improving village governance and strengthening community participation in sustainable rural development.